Molecular cloning of biologically active proviral DNA of the anemia-inducing strain of spleen focus-forming virus. - Kaminchik, J (1982)
Previously, we have molecularly cloned proviral DNA of a polycythemia-inducing strain of the spleen focus-forming virus (SFFVp). In this paper, we report that unintegrated proviral DNA of the anemia-inducing strain of SFFV (SFFVA) has been molecularly cloned into pBR322. This molecularly cloned DNA retains the biological activity of SFFVA, as infectious SFFV can be recovered from the DNA clone by marker rescue using a previously described two-stage cotransfection assay (Linemeyer et al., J. Virol. 35:710-721, 1980). The recovered SFFV retains an important property of the initial SFFVA which distinguishes SFFVA from SFFVP, namely, the ability of SFFVA to cause proliferation of erythroid cells in which hemoglobin synthesis is erythropoietin dependent. By utilizing a marker rescue technique, the splenomegaly and anemia characteristic of SFFVA-induced disease have been traced to a DNA fragment of SFFVA containing sequences coding for the env gene product. gp52. The results suggest that the differences in pathogenicity between SFFVP disease and SFFVA disease are an intrinsic property of the env gene products of these two variants of Friend virus, and future studies with the molecular clones of each strain should allow us to map regions of each env gene responsible for common and distinctive features of the erythroproliferative diseases induced by each virus.